Pediatric chronic myeloid leukemia with inv(3)(q21q26.2) and T lymphoblastic transformation: a case report. Issue 1 (December 2016) - Lewen, Margaret; Gresh, Renee; Queenan, Maria; Paessler, Michele; Pillai, Vinodh; Hexner, Elizabeth; Frank, Dale; Bagg, Adam; Aplenc, Richard; Caywood, Emi; Wertheim, Gerald
Abstract Background Chronic myeloid leukemia (CML) comprises ~3 % of pediatric leukemia. Although therapy with tyrosine kinase inhibitors (TKIs) is highly effective for CML, multiple factors have been identified as predictive of treatment failure. Chromosomal abnormalities involving theMECOM locus at 3q26 portend therapy resistant disease in adults, yet have never been described in pediatric patients and have not been associated with T lymphoblastic progression. Case presentation We present a case of an 11-year-old boy with CML possessing the unique combination of T lymphoblastic transformation and a subclone harboring inv(3)(q21q26.2) at diagnosis. This is the first reported case of pediatric CML with inv(3)(q21q26.2) and the first case of T lymphoblastic progression associated with this karyotype. The patient was treated with single agent TKI therapy with robust initial response. Marrow histology at one month showed restoration of trilineage hematopoiesis andBCR-ABL RT-PCR at three months showed a 1.4 log reduction in transcript levels. Conclusions The karyotypic abnormality of inv(3)(q21q26.2) in CML is not restricted to adult patients. Moreover, while chromosome 3 abnormalities are markers of TKI resistance in adults, our patient showed a robust early response to single agent TKI therapy. This finding suggests pediatric CML with inv(3)(q21q26.2) may have distinct features and more favorable treatment responses than those described in adults.